IELTS READING: STRATEGIES TO BOOST THE SCORE - Mannonova Shahnoza Inomjonovna (Journals Park Publishing, 2023)
The purpose of this article is to analyze the main methods and techniques for improving the quality of reading in English, as well as to develop recommendations for preparing for the IELTS exam in the "Reading" module. IELTS is a test for those who intend to study or practice in an English–speaking environment, it makes it possible to establish the degree of English proficiency in people who are not native speakers.
Keywords: IELTS, reading, reading skills, recommendations, strategies, techniques.